The Patient in Patient Safety: Clinicians' Experiences Engaging Patients as Partners in Safety. Issue 1 (September 2019) - Lerner Papautsky, Elizabeth; Holden, Richard J.; Valdez, Rupa S.; Gruss, Valerie; Panzer, Jeffrey; Perry, Shawna J.
Patients and families play a role in the safety of care provided across clinical settings, highlighting the need to understand clinician perspectives and experiences related to their engagement. Through a panel discussion entitled, The Patient in Patient Safety: Clinicians' Experiences Engaging Patients as Partners in Safety, we elicited clinician perspectives that have implications for human factors relevance in both, research and solution development/evaluation. We provide an overview of the panel including participants, format and content, and the resulting discussion.